Human RIF1-Protein Phosphatase 1 Prevents Degradation and Breakage of Nascent DNA on Replication Stalling - Garzón, Javier; Ursich, Sebastian; Lopes, Massimo; Hiraga, Shin-ichiro; Donaldson, Anne D. (Cell reports (Cambridge), 2019)
RIF1 is a multifunctional protein implicated in controlling DNA replication and repair. Here, we show that human RIF1 protects nascent DNA from over-degradation at stalled replication forks. The major nuclease resecting nascent DNA in the absence of RIF1 is DNA2, operating with WRN as an accessory helicase. We show that RIF1 acts with protein phosphatase 1 to prevent over-degradation and that RIF1 limits phosphorylation of WRN at sites implicated in resection control. Protection by RIF1 against inappropriate degradation prevents accumulation of DNA breakage. Our observations uncover a crucial function of human RIF1 in preventing genome instability by protecting forks from unscheduled DNA2-WRN-mediated degradation. [Display omitted] •Human RIF1 protects nascent DNA at stalled replication forks•PP1 interaction is essential for RIF1 to prevent degradation upon fork stalling•DNA2 nuclease together with WRN helicase mediates resection in the absence of RIF1•DNA2-mediated degradation in cells lacking RIF1 leads to DNA damage Garzón et al. show that human RIF1 protects nascent DNA from DNA2-WRN-mediated degradation upon replication fork stalling. This function depends on RIF1 interaction with PP1 and prevents the accumulation of DNA damage and breaks. This discovery highlights the importance of RIF1 in maintaining genomic stability when DNA replication is challenged.